International marketing in the fast changing world - Sto<U+0308>ttinger, Barbara; Schlegelmilch, Bodo B.; Zou, Shaoming (Bingley, U.K. : Emerald, 2015)
Volume 26 of Advances in international marketing is devoted to a set of papers that attempt to develop new knowledge or refine the existing knowledge to account for the emerging international marketing issues in a fast changing world. These include topics such as dynamic capabilities of international marketers, entrepreneurial orientation, rise of emerging markets MNCs, cultural and institutional distances, organizational learning and knowledge transfer in MNCs, and international marketing strategies in fast changing environments. Collectively, the papers in Volume 26 shed significant light on many emerging issues and form a solid foundation for future research.
Revisiting Uppsala through the lenses of new ventures : a longitudinal study of Norwegian firms / Geir Gripsrud, Auke Hunneman, Carl Arthur Solberg -- Internationalization through e-commerce. The case of multi-brand luxury retailers in the fashion industry / Simone Guercini, Andrea Runfola -- Internationalisation strategies and industry structure / Carl Arthur Solberg, Franc<U+0327>ois Durrieu -- Small-medium sized manufacturers' internationalization through retail store openings abroad : a study of the Italian fashion industry / Simone Guercini, Andrea Runfola -- A taxonomy of export-pricing strategies and their performance in international markets / Katharina Maria Hofer, Lisa Maria Niehoff, Gerhard A. Wu<U+0308>hrer -- Enhancing organizational performance of international SMEs through inter-firm marketing collaborations / Kayhan Tajeddini, Ulf Elg, Pervez N. Ghauri -- Examining causal relationships among international experience, perceived environmental uncertainty, market entry node, and international performance / Hui Xu ... [et al.] -- International marketing in multinational company subsidiaries in emerging markets : a multi-dimensional approach / Debora Atala Pires ... [et al.] -- The moderating roles of organizational learning and strategic flexibility on marketing strategic change and business performance: evidence from firms in Thailand / Amonrat Thoumrungroje -- Impact of acculturation, consumer affinity, and inverse COO effect on a supplier countrys image from exporting professional services to a host country : a conceptual framework / Roy Toffoli ... [et al.] -- Perceived quality of Asian brands by U.S. consumers : case of cosmetic brand using age as a moderator / Sarah (Song) Southworth, Minjeong Kim -- Global brand attitude, perceived value, consumer affinity, and purchase intentions : a multidimensional view of consumer behavior and global brands / Nayyer Naseem, Swati Verma, Attila Yaprak.
Print version record
Keywords: Business & Economics -- International -- Marketing; Business & Economics -- Marketing -- General; Business & Economics -- Marketing -- Research; Sales & marketing management; Export marketing